Creating a Dedicated Pandemic Ambulatory Clinic: Lessons Learned From COVID-19. Issue 2 (21st April 2022) - Kwon, Joshua; Hedges, Mary; Jackson, K. Dawson; Keimig, Andrew; Francis, Dawn
Abstract : Background and Objectives: COVID-19 is highly infectious and the pandemic requires many adaptations to how we deliver medical care. Early in the pandemic, much of this focus was on hospital and emergency department care delivery models to ensure the safety of non–COVID-19 patients and health care workers. However, providing much needed outpatient assessments for COVID-19 patients during a pandemic is also fraught with challenges. From our review of the literature, best practices for a dedicated pandemic ambulatory outpatient clinic have not previously been described. We present a model for creating a dedicated ambulatory pandemic clinic at our institution for the acute care needs of COVID-19 patients. Methods: To address the current pandemic, the Mayo Acute Symptoms of COVID-19 Clinic was implemented on April 13, 2020, with the aims of providing a stand-alone location for COVID-19 patients to have acute outpatient evaluations as well as diagnostics. Results: Recognized challenges addressed included consideration of airflow recirculation patterns in standard medical office buildings, optimization of protocols to conserve personal protective equipment (PPE), limiting total exposure time during patient flow, and reducing surfaces and spaces that patients would physically contact. To this end, unique methods of patient scheduling, patient flow process, staff training, and PPE protocols were developed and are explained in detail in this article. Conclusion: In the COVID-19 pandemic, as well as inevitably in future pandemics, outpatient medical facilities need to be prepared to care for nonhospitalized and nonemergent pandemic patients. We offer a practical approach that has been successful at our institution, with opportunity for local adaptation based on need and resources.